Juvenile Delinquency And The Role Of Institutions In Caring For Them (Journal of the College of Basic Education, 2026)
The problem of juvenile delinquency is one of the most complex and dangerous problems suffered by all societies that have advanced or delayed in scientific and technological progress, and that Iraq has recently increased delinquency as a result of the wars it has been subjected to, as it has brought about major changes in the social life of the individual and society from the deterioration of the standard of living and the high percentage of unemployed and students leaving school seats and engaging in work that is not commensurate with their ages, which makes them vulnerable to delinquency and committing crimes, which prompted government institutions to try to reform and guide them. The family is the first cell in which the child grows and grows up and acquires the culture of society, its customs, traditions and customs, as well as the human need for control and supervision by the father and mother, so the normal personality is not complete unless these two basic elements are available in early childhood, the family rift leads to delinquency, so the juvenile seeks to search for an alternative that satisfies his needs and desires is the street, homelessness, loss and bad companions to represent the alternative to the family, as well as the severity and rigor by the father and the corruption of family morals lead to Same result.The research aims to reach the following:1- Identify the causes, obstacles and the role of institutions in caring for the delinquency.2-Modifying the behavior of juveniles and rehabilitating them professionally, psychologically, educationally and behaviorally.3- Providing solutions and recommendations to the family, society and institutions by providing special programs in the reform and protection of juvenile delinquents.